Kant’s Aesthetic Ideas as Axiological Memory - Râmbu, Nicolae (Con-Textos Kantianos. International Journal of Philosophy, 2018)
By axiological memory I mean the capacity of a society to establish a set of fundamental values in the memory of its people, so that these values become indelible and unforgettable. The thesis that I will argue in this essay is that aesthetic ideas, which are closely related to Kant’s theory about genius and taste from the Critique of Aesthetic Judgement, are values that the genius creates and translates into works of art in order to be set in the collective memory. Aesthetic ideas shape the tastes of others so that the collection of works and especially masterpieces of a particular civilization forms a genuine support for the axiological memory.